Tests of the capital market theory and implications of its evidence: The Philippine stock market - Santos, Rhoderick R. (Animo Repository, 1992)
This paper is an empirical investigation of the Capital Market Theory in the context of the Philippine capital market. The following are observed: a) portfolio risk decreases with an increase in the number of securities in a portfolio, validating the hypothesized risk-size relationship, and b) correlation between a portfolio and the market index increases with an increase in the number of securities in a portfolio, again supporting the hypothesized relationship between size and market correlation. The study also shows that a randomly constructed portfolio will outperform the market (in terms of return on investment) and most portfolios constructed using fundamental analysis. Moreover, a randomly constructed portfolio shows higher correlation to the market and exhibits lower risk than most portfolios constructed using fundamental analysis. Finally, the simulation done on different portfolio sizes points to the reasonableness of maintaining a lean portfolio to maximize portfolio gain. A portfolio of sixteen (16) securities is well diversified with lower risk than the market index and likewise exhibits a respectable correlation of more than 8 percent. In sum, this study provides an operational framework for practitioners, specifically, by defining methods of capital market analysis from security valuation, beta computations, and portfolio composition/management inclusive of the risk-return characteristics of available capital market instruments.